Dynamics of cardiorespiratory response during and after the six-minute walk test in patients with heart failure. (2nd April 2020) - Yoshimura, Kae; Urabe, Yukio; Maeda, Noriaki; Yuguchi, Satoshi; Yoshida, Toshinobu
ABSTRACT: Purpose : The six-minute walk test (6MWT) is a useful measure to evaluate exercise capacity with a simple method. The kinetics of oxygen uptake ( V ˙ O2 ) throughout constant-load exercise on cardiopulmonary exercise testing (CPX) are composed of three phases and the V ˙ O2 kinetics are delayed in patients with heart failure (HF). This study aimed to investigate the kinetics of the cardiorespiratory response during and after the 6MWT according to exercise capacity. Methods : Forty-nine patients with HF performed CPX and the 6MWT. They were divided into two groups by 6MWT distance: 34 patients walked ≥300 m (HF-M), and 15 patients walked <300 m (HF-L). V ˙ O2, minute ventilation ( V ˙ E), breathing frequency, tidal volume, and heart rate, both during and after the 6MWT, were recorded. The time courses of each parameter were compared between the two groups. CPX was used to assess functional capacity and physiological responses. Results : In the HF-M group, V ˙ O2 and V ˙ E stabilized from 3 min during the 6MWT and recovered for 3 min, respectively, after the 6MWT ended. In the HF-L group, V ˙ O2 and VE stabilized from 4 min, respectively, during the 6MWT and did not recover within 3 min after the 6MWT ended. On CPX in the HF-M group, V ˙ O2 peak, and anaerobic threshold were significantly higher, while the relationship between minute ventilation and carbon dioxide production was lower compared with the HF-L group. Conclusion : In lower exercise capacity patients with HF had slower V ˙ O2 and V ˙ E kinetics during and after the 6MWT.